Highly electrochemically‐active surface area of Ni (OH)2 with petal structure in situ grown on conductive Ni foam for efficient hydrogen evolution reaction. (9th August 2021) - Song, Chao; Zhou, Xingwei; Yoo, Seung Jo; Wang, Yan; Zhang, Zunhao; Zhang, Xiaoyu; Kim, Jin‐Gyu; Zhang, Wei
Abstract : An highly electrochemically active surface area and the efficient carrier transfer between catalysts and their carriers are the basis of an efficient hydrogen evolution reaction (HER). Here, petal‐like Ni (OH)2 nanosheets with tunable size and thickness, which represent controllable electrocatalytically active areas, are directly grown on conductive Ni foam. As a result, the optimized in situ‐grown Ni (OH)2 nanosheets (NSNs) show optimum HER performance and stability compared to step‐by‐step‐grown NSNs with similar surface areas due to the enhanced carrier transfer efficiency. The in situ NSNs show high HER activity with overpotentials of 187 and 137 mV with respective current densities of 20 and 10 mA cm −2 in alkaline solution. Our work affords a simple and reliable method for future catalyst design.